Safety, tolerability, pharmacokinetics and pharmacokinetic‐pharmacodynamic modelling of the novel H4 receptor inhibitor SENS‐111 using a modified caloric test in healthy subjects - Venail, Frédéric; Attali, Pierre; Wersinger, Eric; Gomeni, Roberto; Poli, Sonia; Schmerber, Sebastien (British journal of clinical pharmacology, 2018)
Aim A Phase 1 study was performed to evaluate safety, pharmacokinetics (PK) and pharmacodynamics (PD) of the selective histamine H4 receptor antagonist SENS‐111, an oral small molecule. Methods One hundred healthy subjects were randomized in a placebo‐controlled, double‐blind study evaluating single‐ascending doses (SAD; 100–500 mg) and multiple‐ascending doses (MAD; 50–150 mg day−1, 4 days; 200–250 mg day−1, 7 days). Effects of SENS‐111 on nystagmus and vertigo induced by modified caloric tests were measured in the MAD studies. Population PK and PK/PD models were developed using a nonlinear mixed‐effects approach. Results SENS‐111 was well tolerated with mild to moderate events. No sedation was reported. A maximal tolerated dose was not reached. Dose‐proportional increases in concentrations were seen up to 200 mg and more than dose‐proportional thereafter, with mean half‐life between 24 and 56 h. The caloric test induced mild but measurable vertigo and nystagmus with large intra/inter‐individual variation for all parameters. SENS‐111 did not significantly impact nystagmus but significantly improved latency of vertigo appearance/disappearance, duration and European Evaluation of Vertigo questionnaire parameters vs. baseline. A two‐compartment model with first‐order absorption, distribution and elimination best fit the data. PK/PD indirect modelling applied to vertigo duration and latency of appearance indicated maximum activity between 100 and 500 ng ml−1 plasma concentrations, corresponding to 100 and 200 mg day−1, which are appropriate for clinical efficacy evaluations in vestibular diseases. Conclusions SENS‐111 is a well‐tolerated first‐in‐class H4 receptor antagonist with acceptable PK for oral daily dosing. PK/PD modelling determined plasma concentrations and doses for efficacy studies in patients with vertigo symptoms.